PERAN MASYARAKAT DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI MADRASAH - NURLINA Nurlina (Adaara: Jurnal Manajemen Pendidikan Islam, 2018)
Abstrak. Human resource development demands from time to time are increasing. Therefore education services must be able to keep up with these developments. Besides family and school, the community has its own role in education. The role of the community in madrasah education must be carried out jointly to improve the quality of education. So the role in education is not only educators but also the community must contribute to improving the quality of education for the betterment of the nation. Therefore, the community has an important role in achieving a quality education goal. Education as a process requires synergy between components and requires an understanding of the vision of all stakeholders involved. Support from the community is very necessary for the implementation of good education because of the community so that madrasas will become more qualified, because of the support from the community, of course the progress of the madrasa will be reaped through the future of children in the future by involving their role in improving the quality of education services which include planning, supervision and evaluation of education programs including the field of religious education. Keywords:The Role Of The Community In Improving Education Quality